The biologist's imagination : innovation in the biosciences - Hoffman, William R.; Furcht, Leo (OXFORD UNIVERSITY PRESS, 2014)
"Discusses the history of technological innovation in the biosciences"--
"Scholars and policymakers alike agree that innovation in the biosciences is key to future growth. The field continues to shift and expand, and it is certainly changing the way people live their lives in a variety of ways. But despite the lion's share of federal research dollars being devoted to innovation in the biosciences, the field has yet to live up to its billing as a source of economic productivity and growth. With vast untapped potential to imagine and innovate in the biosciences, adaptation of the innovative model is needed. In The Biologist's Imagination, William Hoffman and Leo Furcht examine the history of innovation in the biosciences, tracing technological innovation from the late eighteenth century to the present and placing special emphasis on how and where technology evolves. Place is key to innovation, from the early industrial age to the rise of the biotechnology industry in the second half of the twentieth century. The book uses the distinct history of bioscientific innovation to discuss current trends as they relate to medicine, agriculture, biofuels, stem-cell research, neuroscience, and more. Ultimately, Hoffman and Furcht argue that, as things currently stand, we fall short in our efforts to innovate in the biosciences; our system of innovation is itself in need of innovation. It needs to adapt to the massive changes brought about by converging technologies, globalization in higher education as well as in finance, and increases in entrepreneurship. The Biologist's Imagination is both an analysis of past models for bioscience innovation and a forward-looking, original argument for how future models should be developed"--
Machine generated contents note: -- Introduction -- Chapter 1: Ideas, progress, wealth, and the biological revolution -- Chapter 2: Drugs, biomolecules, brains, and the shifting currents of innovation -- Chapter 3: Regional bioinnovation: Reaping the harvest of the local -- and the global -- Chapter 4: Mendel's journey from peas to petabytes -- Chapter 5: Toning up universities for regional growth -- Chapter 6: Splicing and dicing: Property, information, and the DNA of innovation -- Chapter 7: Looking ahead as an industry evolves -- Conclusion -- Chapter endnotes -- Selected bibliography -- Acknowledgements -- Index.
Includes bibliographical references and index.
Keywords: Biology -- Technological innovations; Life sciences -- Technological innovations; Medical innovations; SCIENCE / Life Sciences / General; Print books